ANALISIS KELAYAKAN PEMBENTUKAN DAERAH OTONOM BARU PERSIAPAN GUNUNG SAHILAN DARUSSALAM KABUPATEN KAMPAR - malau, riki hanri; alkadafi, muammar (Jurnal Niara, 2018)
The object of this research is the plan for the establishment of a new autonomous region of the preparation of Gunung Sahilan Darussalam from Kampar Regency.. The purpose of this research is to know the technical feasibility of expansion Gunung Sahilan Darussalam based on Government Regulation Number 78 Year 2007 About Procedure of Formation, Elimination and Merger of Region. Research methods; Using secondary data and analyzed quantitatively by determining the scores of each indicator into the eligibility requirements, consisting of 11 detailed factors into 35 indicators, then the data will be analyzed descriptively to explain the research results. The results of the study based on the assessment of indicators as mandated by Government Regulation Number 78 Year 2007. The formation of Gunung Sahilan Darussalam Regency can be said less fortunate as a new autonomous region and included in the category rejected to be done expansion. This is because the total score for the candidate of Gunung Sahilan Darussalam Regency only reaches score 334, while the entry in the category of able and recommended if the score or the value reaches at least 340. However, the total for the remaining regency (Kampar after expansion) reaches 401. This means that number Categorized able, and meaningful of Regency of parent (Kampar after expansion) recommended. Thus, if the formation of Gunung Sahilan Darussalam Regency is realized to be non-lethal of the parent Regency (Kampar after expansion), which leaves 14 (fourteen) subdistricts